Design and development of sulfonylurea derivatives as zinc metalloenzyme modulators. Issue 11 (22nd January 2016) - Hadianawala, Murtuza; Datta, Bhaskar
Abstract : Sulfonylurea derivatives are zinc metalloenzyme modulators. Abstract : Sulfonamide derivatives are an important class of zinc metalloenzyme inhibitors. While the sulfonylurea group is a bioisoster of sulfonamide, their effect on the modulation of metalloenzymes has never been studied. In the present work we synthesize and screen new sulfonylurea derivatives towards the zinc metalloenzymes, human Carbonic Anhydrase II (hCA II) and histone deacetylase 1 (HDAC 1). Specific sulfonylurea derivatives are found to inhibit hCA II with IC50 in the nano molar to micro molar range. Docking studies indicate the binding of the inhibitors to the mouth of the active site cavity thereby blocking access to the enzyme. Surprisingly sulfonylurea derivatives exhibit activation of HDAC 1 rather than inhibition. The activation of HDAC 1 is not uniform across the derivatives tested suggesting a specific mode that depends on structural features of the compounds. Extensive research has been performed on HDAC inhibitors due to their potential as anti-cancer agents, however relatively little has been reported in terms of HDAC activation. In this work, we present the distinctly divergent behavior of the same class of molecules namely sulfonylurea derivatives with respect to hCA II and HDAC 1 and attempt to provide an understanding of the same.